Gender Agitation and Anti-sexual Harassment: A Social Prophetic Study of Kuntowijoyo's Perspective View - Perdana Putra Pangestu (Journal of Gender and Millennium Development Studies, 2024)
Sexual harassment and violence seem to be a matter that is still taboo and has not been well internalized in the social area of our society. The prevalence of cases that seem endlessly surfacing in the public eye, forming a massive agitation collectively to eradicate the naughty sexual paradigm. The author is interested in examining how the construction of the movement and the counter-narrative formed in realizing freedom and understanding fundamentally related to sexual harassment. The author takes a qualitative approach, through literature review and existing phenomena. The description of the study will be obtained by optimizing the formulation of the interpretation of topics surrounding the issue of sexual harassment. The elaboration of interpretations and data is then analyzed through Kuntowijoyo's Social Prophetic theoretical line. This research concludes that the various forms of agitation exposed are exposures to building humanization and liberation values for all people fairly and safely.